Image Processing: Review on Face Recognition Approaches - Saini, Dapinty; Sharma, Jagriti (International Journal of Computer Sciences and Engineering, 2025)
Face recognition in image processing is a challenging area in the field of computer vision. We recognize images in an efficient way using various techniques. Some of them are principal component analysis, Blurring techniques and Kernel methods. We present framework of these face recognition techniques and literature review is also provided. We apply wavelet transform on blurring techniques which is further trained with principal component analysis to check recognition rate.